Comparative analysis of first-attack performance in elite women’s volleyball at the 2020 and 2024 Olympic Games - Wang, Meng'Juan; Wang, Jie (Frontiers in Sports and Active Living, 2025)
This study compares and analyzes the performance of elite women's volleyball teams in various aspects of the first attack during the 2020 Tokyo Olympics (OG-20) and the 2024 Paris Olympics (OG-24). It reveals the changing trends in the first attack system of elite women's volleyball teams, particularly in receiving serves, setting, and attacking. By combining video analysis, the study identifies the underlying causes of issues within the first attack system and provides an overall understanding of the development trends of the first attack system in elite women's volleyball. The study findings provide a theoretical basis for coaches to develop targeted training programs and optimize tactics, and serve as a reference for elite women's volleyball teams preparing for the 2028 Olympic Games.